2021
DOI: 10.1039/d1tc04678k
|View full text |Cite
|
Sign up to set email alerts
|

A highly selective gas sensor based on the WO3/WS2 van der Waals heterojunction for the 2-chloroethyl ethyl sulfide (2-CEES) sensing application

Abstract: A highly selective gas sensor based on the WO3/WS2 van der Waals heterojunction for 2-chloroethyl ethyl sulfide (2-CEES) was successfully realized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…It significantly affects the adsorption–desorption phenomenon and reaction kinetics of the target gas with oxygen molecules on the sensor surface by improvising the activation energy in the sensing material. 33 Therefore, investigations were done to test the sensing performance of Zn 1− x Mn x SnO 3 samples by exposing to 500 ppm CO gas at various altered operating temperatures of 50–300 °C. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It significantly affects the adsorption–desorption phenomenon and reaction kinetics of the target gas with oxygen molecules on the sensor surface by improvising the activation energy in the sensing material. 33 Therefore, investigations were done to test the sensing performance of Zn 1− x Mn x SnO 3 samples by exposing to 500 ppm CO gas at various altered operating temperatures of 50–300 °C. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Because the composition and chemical structure of less toxic and less hazardous 2-chloroethyl ethyl sulfide (2-CEES) are similar to those of mustard gas, it is frequently used as a mustard gas simulant. 7…”
Section: Introductionmentioning
confidence: 99%
“…The optimal working temperature for detecting 10 ppm DMMP was 350 °C, and the response time was 26.2 s. 23 A ZnO thick-film sensor fabricated by Patil et al 24 exhibited an optimal operating temperature of 400 °C and a sensitivity of 3 in response to 2 ppm 2-CEES. Fan et al 7 prepared a WO 3 /WS 2 composite structure using a solvothermal method, and its response sensitivity to 5.7 ppm 2-CEES was 81% at an optimal operating temperature of 240 °C. Unfortunately, single metal oxides generally exhibit low sensitivity, selectivity and stability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that when the human body is exposed to an atmosphere of dichlorodiethyl sulfide, it can cause local damage to the skin, eyes, respiratory tract and other parts, and even in low concentrations of dichlorodiethyl sulfide, it will cause death. 3,4 Therefore, effectively detecting low concentrations of dichlorodiethyl sulfide has great importance in both environmental protection and human healthcare. At present, the detection of dichlorodiethyl sulfide mainly adopts ion migration spectrometry, mass spectrometry, gas chromatography, micro-cantilever sensors, surface acoustic wave sensors, quartz-crystal microbalance sensors (QCMs), and fluorescence detection kits.…”
Section: Introductionmentioning
confidence: 99%